2012
DOI: 10.1152/ajplung.00099.2012
|View full text |Cite
|
Sign up to set email alerts
|

RAGE signaling by alveolar macrophages influences tobacco smoke-induced inflammation

Abstract: Receptors for advanced glycation end-products (RAGE) are multiligand cell surface receptors of the immunoglobin family expressed by epithelium and macrophages, and expression increases following exposure to cigarette smoke extract (CSE). The present study sought to characterize the proinflammatory contributions of RAGE expressed by alveolar macrophages (AMs) following CSE exposure. Acute exposure of mice to CSE via nasal instillation revealed diminished bronchoalveolar lavage (BAL) cellularity and fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…The siRNA inhibition of RAGE expression decreased CSE-induced NFkB activation and cytokine secretion (Reynolds et al, 2011). Further evidence indicated that elevated levels of RAGE in alveolar macrophages was accompanied by an increased expression of active Ras and proinflammatory cytokines, which were reduced in RAGE-deficient alveolar macrophages (Robinson et al, 2012b;Chen et al, 2013). Together, these findings suggest that RAGE may mediate the effects of cigarette smoking or CSE on airway and pulmonary inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…The siRNA inhibition of RAGE expression decreased CSE-induced NFkB activation and cytokine secretion (Reynolds et al, 2011). Further evidence indicated that elevated levels of RAGE in alveolar macrophages was accompanied by an increased expression of active Ras and proinflammatory cytokines, which were reduced in RAGE-deficient alveolar macrophages (Robinson et al, 2012b;Chen et al, 2013). Together, these findings suggest that RAGE may mediate the effects of cigarette smoking or CSE on airway and pulmonary inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…Epithelial cells were also found to produce substantial numbers of MVs, but with delayed kinetics compared with alveolar macrophages. It has been previously suggested that epithelial cell-derived MVs are upregulated in BALF in patients with ARDS at 6 hours after intubation for respiratory failure,12 although these MVs were identified by expression of the receptor for advanced glycation end products (RAGE), and would likely represent a mixture of cell origins as various lung cells express RAGE 34. CD11b + /Ly6G + MVs were only apparent at 4 hours in our model of LPS-induced ALI, suggesting that these are MVs produced by infiltrating neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The elastin mRNA expression can be induced by the TGF-␤ receptor/ Smad signaling pathway and stabilized by the active protein kinases p38 and/or PKC␦ (11,27). Out of these factors p38 was reported to be involved in RAGE signaling (7,42,50). Therefore, it is well conceivable that sRAGE/RAGE contributes to higher elastin levels via p38 action.…”
Section: Discussionmentioning
confidence: 99%